Effectiveness of Archive Arrangement in the Barru Regency Regent's Office - Nasrullah, Muh; Suci Amalia, Dian; Arhas, Sitti Hardiyanti (Pinisi Journal of Education and Management, 2023)
Archives for an agency are one of the supports for the smooth running of operational activities. Archives are one of the most valuable assets owned by an agency and carry a large role for the agency. This research aims to find out how effective the organization of archives at the Barru Regency Regent's Office is in-depth and detail, equipped with supporting and inhibiting factors. This research is qualitative, therefore, to achieve the research objectives, data collection techniques were used, namely observation, interviews, and documentation with informants, 3 employees in the Archives Section of the Barru Regency Regent's Office. The results of this research show that all indicators used in this research are classified as effective. The indicator referred to is that active inspection is classified as effective because incoming files are first checked properly and thoroughly based on the number or alphabet used. Indexing archives is considered effective because the files are checked and then stored in folders with the same captured words or keywords. Giving marks is considered effective because the archives are marked in the form of bright-colored sticky notes. Sorting archives is considered effective because files that have been classified based on keywords are put into folders. Archive storage is classified as effective because the files have been organized well and carefully from the beginning to the last stage, namely storing employee records in folders and then storing the folders in archive cabinets. In this research, several indicators are used that can answer the research problem formulation from the initial stage to the final stage in arranging in-depth and detailed archives at the Barru Regency Regent's Office. The results of research using several indicators can reveal the process of structuring archives from the initial process to the final process, equipped with supporting factors and inhibiting factors contained in the process of structuring archives at the Barru Regency Regent's Office.